2020
DOI: 10.1007/s40266-020-00783-w
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability Results from the PILLAR Study: A Phase IV, Double-Blind, Randomized, Placebo-Controlled Study of Mirabegron in Patients ≥ 65 years with Overactive Bladder-Wet

Abstract: Background In older patients with overactive bladder (OAB), mirabegron, a β 3-adrenoreceptor agonist, represents an alternative treatment that may have a favorable risk-benefit profile. Objectives Our objective was to further examine the safety and tolerability of mirabegron versus placebo treatment in patients aged ≥ 65 years with OAB-wet. Methods We conducted a 12-week, double-blind, randomized, placebo-controlled phase IV study to compare mirabegron with placebo. Community-dwelling patients aged ≥ 65 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…The efficacy of mirabegron in patients aged >65 years was assessed in a large double-blind, randomized, placebo-controlled, multicenter study that enrolled 888 subjects with OAB wet in the US and Canada.After 12 weeks of treatment, the authors found significant superiority of mirabegron over placebo with respect to reduction in frequency, number of urgency and incontinence episodes, and mean voided volume. 43 These findings are consistent with those published previously, which reported a pooled analysis of patients aged >65 years enrolled in three phase III studies. 44 These data were also supported by work of Lozano-Ortega et al who proved that mirabegron was similarly as effective as ACh across all efficacy end points in an older population.…”
Section: Mirabegronsupporting
confidence: 92%
“…The efficacy of mirabegron in patients aged >65 years was assessed in a large double-blind, randomized, placebo-controlled, multicenter study that enrolled 888 subjects with OAB wet in the US and Canada.After 12 weeks of treatment, the authors found significant superiority of mirabegron over placebo with respect to reduction in frequency, number of urgency and incontinence episodes, and mean voided volume. 43 These findings are consistent with those published previously, which reported a pooled analysis of patients aged >65 years enrolled in three phase III studies. 44 These data were also supported by work of Lozano-Ortega et al who proved that mirabegron was similarly as effective as ACh across all efficacy end points in an older population.…”
Section: Mirabegronsupporting
confidence: 92%
“…An in-depth examination of the safety and tolerability of mirabegron among the participants in the PILLAR study demonstrated a frequency of TEAEs (47%) similar to that of previously reported phase III studies enrolling patients aged >65 years. 57 Those TEAEs most frequently reported (UTI, headache, and diarrhoea) were in line with the known mirabegron safety profile, and did not appear to be either age, or dose dependent. Furthermore, a pre-planned analysis aimed to detect potential cognitive decline related to treatment with mirabegron, using a rapid screening instrument for mild cognitive impairment, the Montreal Cognitive Assessment (MoCA), was conducted as part of the PILLAR study.…”
Section: Mirabegronsupporting
confidence: 59%
“…This class of drugs is actively being tested in clinical studies for metabolic diseases [ 109 , 110 ] and CL-316,243 has been previously investigated in humans as well [ 111 ]. As an example, mirabegron (Myrbetriq®) has been approved by the Food and Drug Administration for the treatment of overactive bladder [ 41 , 112 ], and large randomized controlled trials have confirmed its safety and tolerability profiles [ 113 ], even in the elderly population [ 114 ]. Thus, the potential translation to clinical use of this class of drugs in AD is high.…”
Section: Discussionmentioning
confidence: 99%